A new hypothesis for the amount and distribution of dextral displacement along the Fish Lake Valley–northern Death Valley–Furnace Creek fault zone, California‐Nevada. Issue 2 (26th April 2013) - Renik, Byrdie; Christie‐Blick, Nicholas
Abstract [1] The Fish Lake Valley–northern Death Valley–Furnace Creek fault zone, a ~250 km long, predominantly right‐lateral structure in California and Nevada, is a key element in tectonic reconstructions of the Death Valley area, Eastern California Shear Zone and Walker Lane, and central Basin and Range Province. Total displacement on the fault zone is contested, however, with estimates ranging from ~30 to ~63 km or more. Here we present a new synthesis of available constraints. Preextensional thrust faults, folds, and igneous rocks indicate that offset reaches a maximum of ~50 km. Neogene rocks constrain its partitioning over time. Most offset is interpreted as ≤ ~13–10 Ma, accruing at ~3–5 mm/yr in the middle of the fault zone and more slowly toward the tips. The offset markers imply ~68 ± 14 km of translation between the Cottonwood Mountains and Resting Spring–Nopah Range (~60 ± 14 km since ~15 Ma) through a combination of strike slip and crustal extension. This suggests that a previous interpretation of ~104 ± 7 km, based on the middle Miocene Eagle Mountain Formation, is an overestimate by ~50%. Our results also help to mitigate a discrepancy in the ~12–0 Ma strain budget for the Eastern California Shear Zone. Displacement has previously been estimated at ~100 ± 10 km and ~67 ± 6 km for the Basin and Range and Mojave portions of the shear zone, respectively. Our new estimate of ~74 ± 17 km for the Basin and Range is within the uncertainty of the Mojave estimate.